2021
DOI: 10.3389/fbioe.2021.662655
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Responses of a Model Green Microalga Euglena gracilis to Different Environmental Stresses

Abstract: Euglena gracilis, a green microalga known as a potential candidate for jet fuel producers and new functional food resources, is highly tolerant to antibiotics, heavy metals, and other environmental stresses. Its cells contain many high-value products, including vitamins, amino acids, pigments, unsaturated fatty acids, and carbohydrate paramylon as metabolites, which change contents in response to various extracellular environments. However, mechanism insights into the cellular metabolic response of Euglena to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 76 publications
4
16
0
Order By: Relevance
“…PRM and streptomycin are aminoglycoside antibiotics, and streptomycin has a known inhibitory effect on E. gracilis growth (Kirk, 1962). However, this study showed that low concentrations (1-25 μg/ml) of PRM had little effect on E. gracilis growth, suggesting that E. gracilis is tolerant to low PRM concentrations, consistent with previous reports on Euglena antibiotic tolerance (Kirk, 1962;He et al, 2021). E. gracilis could grow mixotrophically; that is, it can first use organic carbons in the medium or field waters instead of CO 2 via photosynthesis under the light.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PRM and streptomycin are aminoglycoside antibiotics, and streptomycin has a known inhibitory effect on E. gracilis growth (Kirk, 1962). However, this study showed that low concentrations (1-25 μg/ml) of PRM had little effect on E. gracilis growth, suggesting that E. gracilis is tolerant to low PRM concentrations, consistent with previous reports on Euglena antibiotic tolerance (Kirk, 1962;He et al, 2021). E. gracilis could grow mixotrophically; that is, it can first use organic carbons in the medium or field waters instead of CO 2 via photosynthesis under the light.…”
Section: Discussionsupporting
confidence: 90%
“…Its cells contain many high-value bioproducts, including vitamins, amino acids, unsaturated fatty acids, and paramylon (Grimm et al, 2015;Zakryś et al, 2017). E. gracilis is of considerable environmental importance and biotechnological value: it can survive a variety of carbon resources, toxic chemicals, and adverse environmental conditions such as heavy metals, antibiotics, acid, salinity, and high levels of ionizing radiation, and can be observed in most waters such as ponds, fish farms and small rivers (Rodríguez-Zavala et al, 2007;Kottuparambil et al, 2012;Mukaida et al, 2016;Moreno-Sánchez et al, 2017;He et al, 2021). Indeed, E. gracilis exhibits remarkable metabolic diversity, blooming as photosynthetic autotrophy, heterotrophy, and photoheterotrophy (Zakryś et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increased metabolism and ATP generation may be a possible mechanisms for recycling oxidized GSH that has already participated in mitigating ROS stress or generating new reduced GSH to sequester Hg(II). The low abundance of fatty acids in Hg treated cells observed in this study is contradictory to other studies where microalgae were exposed to cadmium (Puente-Sánchez et al, 2018), but consistent with fatty acid degradation in E. gracilis after cadmium treatment (He et al, 2021). Essential amino acids also serve as precursors for the generation of ATP through the TCA cycle (Martínez-Reyes & Chandel, 2020), which offers another possible explanation for increased amide and peptide metabolic and biosynthetic processes observed (Table 1).…”
Section: Cellular Respiration and Electron Transportsupporting
confidence: 68%
“…Significant fold-changes in amino acids like cysteine, glutamine, proline, and serine; all amino acids were enriched after Hg treatment, especially in extracellular fractions (Figures 1C,F). The increase in transcripts corresponding to ribosomal proteins like RPL21 and RPS10 further suggests a shift towards increased protein synthesis, which could assist E. gracilis with a variety of processes like metal detoxification, mitigation of reactive oxygen species, and repairing cellular damage (He et al, 2021). Many of the intermediates in metabolic processes are involved in reactions that generate amino acids and other metabolites that are linked to both detoxification and biosynthesis processes (Ishikawa et al, 2017).…”
Section: Enriched Metabolism Translation and Production Of Amino Acidsmentioning
confidence: 99%
“…The bacterial media during logarithmic growth was collected for metabolic analysis. The metabolites in the sample were extracted and analyzed according to the method mentioned by He et al ( 16 ). Each sample group included four biological replicates.…”
Section: Methodsmentioning
confidence: 99%